Helminthes detected from wild sika deer (Cervus nippon centralis) in Kanto-Chubu region, Japan. (April 2022) - Inoue, Ken; Shishida, Kohei; Kawarai, Shinpei; Takeda, Shiro; Minami, Masato; Taira, Kensuke
Abstract: The helminth fauna of 105 sika deer ( Cervus nippon centralis ) captured in Yamanashi, Kanagawa and Nagano Prefectures, Japan was investigated during 2014–2019. As a result, 12 helminthes, i.e. 3 digeneans ( Ogmocotyle sikae, Dicrocoelium chinensis and D. dendriticum ), 8 nematodes ( Gongylonema pulchrum, Dictyocaulus sp., Pygarginema sp., Spiculopteragia houdemeri, Chabaudstrongylus ninhae, Trichuris discolor, Oesophagostomum sikae and Oes. asperum ), and 1 cestode ( Moniezia sp.) were detected. To our knowledge, this is the first report of Pygarginema sp., Cha. ninhae, and Oes. asperum from sika deer in Japan. Some helminthes detected in the present study can infect livestock. Considering the possibility of the spread of the helminthes to livestock through deer excrement, it is important to promote understanding the parasite fauna in wild deer.